English learning application for slow learner - Nurul Naqiyaah, Omar (2015)
English language usage in our country is almost equally to national language which is Malay Language. Various learning methods had been created and one of it is learning application but the application is limited and rarely found in nowadays market. ELASL is a study to developed English learning skills for slow learner patients. ELASL help the Slow Learner to develop the skills by providing an attractive and interactive learning application with complete elements of multimedia with simple navigations and easily understand instruction. ELASL is developed in order to overcome the problem which is there not many multimedia learning resources for slow learners.